Antioxidante natural de erva mate na conservação da carne de frango in vivo - Padilha, Ana Denize Grassi (2007)
The objective of this study was to verify the influence of the natural antioxidant, hidro-etanolic extract of yerba-mate (Ilex paraguariensis St. Hil), on the lipid oxidation, cholesterol content and profile of the fatty acids, of the meat of cut chickens, when submitted the dietary with natural antioxidant. The results of cholesterol assays the of chicken breast had varied of 32.17 the 52.90 mg/100g of meat, and 42.21 the 68.59 mg/100g of meat in the thigh cuts. The treatment with 0,3% of natural antioxidant for the chicken breast differed from the others treatments, getting low the cholesterol. The results of the test of inhibition of the oxidation had been of 21.81%, 63.64% and 50.91% respectively for 0.3%, 0.5% and 0.7% of the natural antioxidant. The treatment with 0.7% of natural antioxidant, has presented the greater total phenols concentration (10.56g/ml), followed for treatments 0.5% (7.71g/ml) and 0.3% (5.29g/ml). The natural antioxidant provided a reduction of the cholesterol in the chicken meat, behavior that can be explained by potential the biological effect of phenolic composites as kidnapping of free radicals, acting in such a way in the stage of initiation as in the propagation of the oxidation process. These results suggest, therefore, an antioxidant effect of phenols identified in the extract hidro-etanolic of yerba-mate, on the mechanism of formation of the in vivo cholesterol of chickens. The natural antioxidant exerted a preponderant influence on the oxidation quality of the chicken meat, during the period of storage under refrigeration and freezing. The values of pH if had kept normal, the TBARS (2-thiobarbituric acid) suffered to a considerable increase with variation from 0.117- 1.053mg of malondialdehyde /kg and 0.078-0.780mg of alondialdehyde /kg for breast and thigh of chicken respectively, indicating reduction in the oxidation speed of the meat. In the period of freezing the values of TBARS for the thigh cut, (trat. 0.3%), greater stability was observed, an variation of 0.117-0.234 mg of malondialdehyde /kg until the two months of freezing, after this period was raised until 0.780mg of malondialdehyde /kg. The prolife fatty acid polyunsaturated n-3, in the cuts of chest of chicken (trat.0.3%) and greater insaturated fatty acid content. Was observed twenty six (26) fatty acid in the cuts of the breast and thigh of chicken. The fatty acid, C16:1, C18:1 , C18:2, C22:5 (DPA), C18:3 e C20:4, they had been found in greater porcentage that the other fatty acid in the cuts of chicken breast (trat. 0.3%) the percentage acid monoinsaturado oleic, of the family n-9, it presented higher level (2.10g/100g) that the observed in literature. Of this form it is possible to consider the use of the natural antioxidant of yerba-mate, with the purpose to have meats and products meat with important functional properties for the health human being.